Health Risk Assessment of Heavy Metals in a Vegetable Cultivated on Land Polluted through Illegal Mining - , A. I. Yaradua, J. I. Bungudu, L. Shuaibu, A. Nasir, A. Usman, I. H. Kankia, N. U. Matazu, Z. A. Suleiman, A. A. Sada, F. A. Rumah, U. Bello, A. B. Tukur; et al. (Archives of Current Research International, 2023)
The risk of exposure to the population from heavy metals in an area that have witnessed a surge in illegal mining activities, cattle rustling and banditry were evaluated in the current study. Lettuce leaves sample from Gadirge village, Jibia local Government area, Katsina State, Nigeria was evaluated for the presence of heavy metals using Atomic Absorption Spectrophotometry. The health risks of the evaluated heavy metals in the sample to the population were assessed using the Target Hazard Quotient (THQ) and Health Risk Index (HRI)) to assess the possible non-carcinogenic effect and the Incremental Lifetime Cancer Risk (ILCR) for the cancer risks. The result of the mean concentration values of the evaluated heavy metals Fe and Pb from the sample falls above the Maximum Allowable Concentrations (MAC) of heavy metals in leafy vegetables. The concentrations of the other metals including Cu, Zn, Ni, Mn and Cd evaluated in the sample were within the permissible values. The result of the Target Hazard Quotient (THQ) associated with the evaluated heavy metals exposure through consumption of the sample for adults and children were all lower than 1, with exception of the THQ for the heavy metals Fe and Mn in the adults and children population that was above 1. The combined health risks for all the metals in the sample for the adults and children population represented as the HRI were higher than 1, the result of the Incremental Life Cancer Risk (ILCR) for both the adult and children population has revealed that the heavy metal Ni was beyond the threshold of the safety limit for cancer risk. There is a health risk concern from consumption of the sample as the vegetable may contribute to the disease burden of the population.